IMPROVEMENT OF PEDAGOGICAL PRACTICE IN THE CONDITIONS OF DIGITAL TECHNOLOGIES (SCIENCE TIME JOURNAL, 2024)
This article explores strategies for improving pedagogical practice in a digital environment. As digital technologies continue to evolve and become integral to education, it is crucial for educators to adapt their instructional approaches to leverage the potential of these tools effectively. The article discusses various aspects of pedagogical practice in a digital context, including mobile learning, data privacy and security, artificial intelligence, coding and computational thinking, online professional learning communities, ethical considerations, and digital literacy. It emphasizes the importance of aligning technology use with learning goals, promoting inclusive practices, and fostering critical thinking skills. The article concludes by highlighting the need for continuous professional development and collaboration among educators to maximize the benefits of digital technologies in education.